2021
DOI: 10.1021/acs.iecr.0c05238
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Self-Healable Siloxane Elastomers Constructed by Multiple Dynamic Bonds for Stretchable Electronics and Microsystems

Abstract: Self-healable siloxane elastomers have recently attracted much interest in research for applications in flexible electronic devices. However, it remains a challenge for self-healable siloxane elastomers to realize good mechanical and rapid high-efficiency selfhealable properties at room temperature. Herein, a desirable siloxane polymer elastomer was designed by the synergy of multiple dynamic bonds. In this self-healable system, the disulfide bonds as sacrificial bonds and hydrogen bonds as weak bonds could en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…These values are far superior to other reported silicone elastomers (with a maximum strength of 5 MPa) (Fig. 2d), 19,23,24,30,36,53–59 and even better than silicone/polyurethane composites that are prepared via tedious and elaborate synthesis. 26,60,61 The toughness of this designed elastomer can reach 25–28 MJ m −3 , which is higher than the reported values of ∼5 MJ m −3 and ∼16 MJ m −3 for silicone elastomers.…”
Section: Resultscontrasting
confidence: 58%
“…These values are far superior to other reported silicone elastomers (with a maximum strength of 5 MPa) (Fig. 2d), 19,23,24,30,36,53–59 and even better than silicone/polyurethane composites that are prepared via tedious and elaborate synthesis. 26,60,61 The toughness of this designed elastomer can reach 25–28 MJ m −3 , which is higher than the reported values of ∼5 MJ m −3 and ∼16 MJ m −3 for silicone elastomers.…”
Section: Resultscontrasting
confidence: 58%
“…It also has to be mentioned that, because of the reversible nature of S−S and H-bonds, they can effectively dissipate strain energy via constant breaking and regrouping during stretching, thereby enhancing the toughness. 37 The slight decrease in the elongation at break with the increase of ADS is due to the constrained chain movement by hard segments during stretching. Nevertheless, the toughness and strain at break (i.e., stretchability) of S-PUUs obtained in this study are significantly higher than other PUs previously reported in the literature (Figure 2d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To further improve the mechanical properties of mPDMS/PEG elastomers, strengthening the network structure while maintaining the good electrical conductivity of the elastomer is crucial. It is noticeable that in our hydrogel research, the multibond network (MBN) strategy is proposed for the preparation of high-strength and stretchable hydrogels. Typically, MBN hydrogels possess a single network composed of hierarchical cross-linking bonds with various binding energies, such as metal–ligand coordination interactions, hydrogen bonding, hydrophobic associations, etc., and these dynamic bonds have been utilized as energy dissipation units and dynamic cross-linking points for network homogeneity through their recombining to reinforce MBN hydrogels. …”
Section: Resultsmentioning
confidence: 99%